Analysis of 1997 Coordinated Portfolio Investment Survey Results and Plans for the 2001 Survey. (World Economic and Financial Surveys; World Economic and Financial Surveys, 2000)
Analysis and Plans, presents an assessment of 1997 survey data and a summary of improvements introduced, as a result of countries' participation in the 1997 Coordinated Portfolio Investment Survey, into national systems for collecting data on international (cross-border) portfolio investment The chapter reviews developments that occurred in international financial markets in the 1980s and 1990s, and the Godeaux Report assessment and recommendations about global data on international portfolio investment flows and stocks. The objectives set for the 1997 survey, the scope of survey results, and the process by which results have been assessed in the chapter. Since publication of the Godeaux Report, substantial expansion and evolution have occurred in exchange and over-the-counter markets for financial derivatives covering a range of financial risks. These markets now have the capacity, in effect, to change the currencies, maturities, and marketability of the financial instruments underlying associated derivative contracts. It is recommended that vigorous efforts should be made to secure the participation of more major investing countries in order to address the under-reporting of global portfolio investment assets and to confirm the reliability of the global data on portfolio investment liabilities.